Makna Simbolik Busana Tari Piring Di Sanggar Siti Nurbaya Kota Surabaya - Bimo Ari Prabowo; Autar Abdilah; Anbie Haldini (Institut Seni Indonesia Yogyakarta, 2026)
The Symbolic Meaning of Plate Dance Clothing at Sanggar Siti Nurbaya, Surabaya City. This research aims to explore the symbolic meaning of the Piring Dance clothing displayed at Sanggar Siti Nurbaya, Surabaya, as an effort to preserve the Minangkabau tradition outside its homeland. The method used in this study is qualitative, by collecting data through observation, in-depth interviews, and documentation. The analysis was carried out by applying the semiotic theory of Roland Barthes which includes three layers of meaning, namely denotation, connotation, and myth. The findings of this study reveal that the clothes of female dancers, such as tikuluak talakuang, tikuluak tanduak, brooches, telephone subang earrings, gadang necklaces, kebaya kurung, and songket sarongs, symbolize the modesty, elegance, and honor of Minangkabau women. Meanwhile, the male dancers' outfits consisting of baju kurung, deta, sarawa galembong pants, and songket sarongs reflect authority, courage, and agility. The colors red, black, and gold symbolize courage, authority, and prosperity. The myth that has been formed shows that the Piring Dance outfit is a representative of the Minangkabau cultural identity that continues to maintain traditional values and Islamic teachings. This clothing not only serves as a complement to the show, but also as a means to preserve cultural values for the younger generation.Keywords: Symbolic Meaning, Dance Clothing, Plate Dance, Semiotics, Minangkabau